Reflex\~oes sobre o papel da política agrícola Brasileira para o desenvolvimento sustentável - Junior Ruiz Garcia; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The study seeks to analyze the importance of agricultural trade policy in Brazil for economic development, discussing issues such as food security, poverty reduction and inequality, employment creation, mitigation and adaptation to climate change and environmental sustainability. The problem aims to question the contributions of Brazil's agricultural trade policy for sustainable development. The hypothesis is understood that agricultural trade policy can be an important tool for development, reducing inequalities and promoting sustainable management of natural resources in Brazil.
Keywords: Q1; Q17; Q28; 330; agricultural policy; development; food security